Polymerization of lignosulfonates by the laccase-HBT (1-hydroxybenzotriazole) system improves dispersibility - Prasetyo, E. N. (2010)
The ability of laccases from Trametes villosa (TvL), Myceliophthora thermophila (MtL), Trametes hirsuta (ThL) and Bacillus subtilis (BsL) to improve the dispersion properties of calcium lignosulfonates 398 in the presence of HBT as a mediator was investigated. Size exclusion chromatography showed an extensive increase in molecular weight of the samples incubated with TvL and ThL by 107% and 572% from 28400 Da after 17 h of incubation, respectively. Interestingly, FTIR spectroscopy, 13C NMR and Py-GC/MS analysis of the treated samples suggested no substantial changes in the aromatic signal of the lignosulfonates, a good indication of the ability of TvL/ThL-HBT systems to limit their effect on functional groups without degrading the lignin backbone. Further, the enzymatic treatments led to a general increase in the dispersion properties, indeed a welcome development for its application in polymer blends.